Halal Tourism in West Sumatera: a Bibliometric Study - Mardian, Sepky; Armen, Rio Erismen (Journal of Business & Banking, 2023)
West sumatera is a halal tourism destination in Indonesia. It was acknowledged by Global Muslim Travel Index in 2016. All stakeholders have given more intention to this halal tourism. Beyond the strengthening district regulation on it, the studies on halal tourism in West Sumatera have been increasing every year. This study aims to map the research about halal tourism in West Sumatera. Bibliometric approach was conducted to map the different studies on this topic. By using Publich or Perish, the data were taken from Google Scholar database. Several keywords were used to do it, i.e. halal tourism in West Sumatera, Islamic tourism in West Sumatera, wisata halal di Sumatera Barat and wisata Sariah di Sumatera Barat. The metadata were described by tables and graphs. Again it is also visualized by VOSViewer to find the research cluster on the topic and trend of relationship among the keywords. The study found that the research on Islamic tourism in West Sumatera is still limited. It only found 35 journal articles or proceeding in tens of years. The theme is also limited on description of the opportunity and challenges and stakeholders perception about Islamic tourism in West Sumatera.